The wolf of Sarajevo - Palmer, Matthew, 1966- (G. P. Putnam's Sons, 2016)
A riveting novel of international suspense from acclaimed author and veteran diplomat Matthew Palmer. Twenty years after the Srebrenica massacre that claimed the life of his friend and colleague, Eric Petrosian is back in Sarajevo at the American embassy, and the specter of war once again hangs over the Balkans. The Bosnian Serb leader, who had for a time been seeking a stable peace, has turned back to his nationalist roots and is threatening to pull Bosnia apart in a bloody struggle for control . . . and behind him is a shadowy mafia figure pulling the strings. As Eric is dragged deeper into the political maelstrom and uncovers a plot of blackmail and ruthless ambitions, Eric is faced with an impossible choice: use the information he's uncovered to achieve atonement for the past or use it to shape the future.